2016
DOI: 10.1111/jpn.12579
|View full text |Cite
|
Sign up to set email alerts
|

Potential of plant polyphenols to combat oxidative stress and inflammatory processes in farm animals

Abstract: Polyphenols are secondary plant metabolites which have been shown to exert antioxidative and antiinflamma tory effects in cell culture, rodent and human studies. Based on the fact that conditions of oxidative stress and inflammation are highly relevant in farm animals, polyphenols are considered as promising feed additives in the nutrition of farm animals. However, in contrast to many studies existing with model animals and humans, potential antioxidative and antiinflammatory effects of polyphenols have been l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
198
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(235 citation statements)
references
References 201 publications
(268 reference statements)
4
198
2
3
Order By: Relevance
“…Treating macrophages with OBE before the stimulation with LPS partly counteracted such responses by about 30%. These results are similar to findings from recent studies demonstrating anti-inflammatory properties of polyphenols and other plant bioactives in cell cultures [52; 53] and farm animals [54]. Furthermore, our in vivo and in vitro results indicate that inhibition of IL1B production is a key component of the OBE anti-inflammatory action.…”
Section: Discussionsupporting
confidence: 92%
“…Treating macrophages with OBE before the stimulation with LPS partly counteracted such responses by about 30%. These results are similar to findings from recent studies demonstrating anti-inflammatory properties of polyphenols and other plant bioactives in cell cultures [52; 53] and farm animals [54]. Furthermore, our in vivo and in vitro results indicate that inhibition of IL1B production is a key component of the OBE anti-inflammatory action.…”
Section: Discussionsupporting
confidence: 92%
“…Epigallocatechin gallate (EGCG), the most active substance in tea polyphenols, demonstrates the strong antioxidant activity and antiinflammatory capacity (Gessner, Ringseis, & Eder, 2017). Extensive research performed in recent years has revealed that EGCG exhibits a strong antioxidant capacity to mitigate the effects of heat stress on growth performance (Luo et al, 2018;Orhan et al, 2013) and meat quality (Huang, Zhang, Zhou, Wan, & Zhang, 2015;Zhang et al, 2012) in poultry.…”
Section: Introductionmentioning
confidence: 99%
“…However, as mRNA concentrations of these genes were not statistically significant different between the two groups of cows, the effect of polyphenols on hepatic inflammation and ER stress remains unclear. As polyphenols are exerting a broad spectrum of metabolic effects [1416], we hypothesized that feeding of GSGME might influence other metabolic pathways in the liver which could account for the positive effects of GSGME observed in cows during early lactation. In order to investigate this hypothesis, we used a genome-wide transcript profiling technique to explore changes in the hepatic transcriptome of cows supplemented with GSGME during the transition period.…”
Section: Introductionmentioning
confidence: 99%